Chaotic Control of Network Traffic - 杨谈 崔毅东 金跃辉 程时端 (Chinese physics letters, 2009)
A method of chaotic control on network traffic is presented. By this method, the chaotic network traffic can be controlled to a pre-assigned equilibrium point according to chaotic prediction and the largest Lyapunov exponent of the traffic on congested link is reduced, thereby the probability of traffic burst and network congestion can be reduced. Numerical examples show that this method is effective.